PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PEGAWAI NEGERI SIPIL DALAM KOORDINASI ASISTEN III KABUPATEN LOMBOK TIMUR - Karyagus Sugandi (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This study is based on two-factor theory of Herzberg aimed to explore the influence of motivation on job satisfaction and employee performance at the Local Government institutions. This type of research used in this study is exploratory. The population of as many as 108 employees with a total sample of 51 of Civil Servants in East Lombok regency Regional Secretariat on the work unit is in the coordination of the General Administrative Assistant III. The sampling technique used is the technique Proportionate Stratified Random, data analysis using Partial Least Square (PLS) using software SmatPLS 3. The results stated that the motivation positive and significant impact on performance, motivation positive and significant impact on job satisfaction, job satisfaction and a positive effect significantly to the performance, motivation indirect effect on performance through job satisfaction as a variable intervenig. The implications of this research uses only motivating factor of two-factor theory also has other limitations that situational variables. work behavior and work is an integral Herzberg assume a correlation between satisfaction and productivity. However, research conducted by Herzberg emphasis on customer satisfaction and productivity neglect. Keywords: Motivation, Job Satisfaction, Employee Productivity, Partial Least Square